Analysis of a Novel Two-Lane Hydrodynamic Lattice Model Accounting for Driver's Aggressive Effect and Flow Difference Integral. (30th May 2020) - Qi, Xinyue; Ge, Hongxia; Cheng, Rongjun
Abstract : In the actual traffic environment, the driver's aggressive driving behaviors are closely related to the traffic conditions at the next-nearest grid point at next time step. The driver adjusts the acceleration of the driving vehicle by predicting the density of the front grid points. Considering the driver's aggressive effect and the relative flow difference integral, a novel two-lane lattice hydrodynamic model is presented in this paper. The linear stability method is used to analyze the current stability of the new model, and the neutral stability curve is obtained. The nonlinear analysis of the new model is carried out by using the theory of perturbations, and the mKdV equation describing the density of the blocked area is derived. The theoretical analysis results are verified by numerical simulation. From the analysis results, it can be seen that the driver's aggressive effect and the relative flow difference integral can improve the stability of traffic flow comprehensively.